Análise geomorfológica e ambiental da Bacia Hidrográfica do Rio Tatuí - Machado Junior, Claudio (2025)
This work is an environmental geomorphology research that was based on the geomorphological analysis of the Tatuí River Watershed, located in the southeastern portion of the state of São Paulo between the municipalities of Tatuí, Itapetininga, Guareí, and Quadra. In addition to the geomorphological analysis elaborated from the identification of landform patterns, the research also addressed the main environmental impacts that occur in the watershed, integrating them into the analysis of Environmental Fragility. The methodology used in this work was based on theoretical references from Geomorphology and Geography, dealing with the taxonomic classification and levels of approach to relief. The Systemic Approach was chosen as the conceptual foundation for the problematization and interpretation of the observed data. The adopted methodology comprises the set of techniques and procedures applied during the analysis, serving as a basis for conducting the research. There was a bibliographic review of the theme, elaboration of thematic maps, and fieldwork. As a result, it was found that in the referred watershed there are 5 (five) units, whose diverse characteristics are, in general, related to the different rocks found in its territory. Furthermore, the lithological contacts themselves impose conditions on the action of the area's drainage network, establishing different levels of dissection. Structural aspects, such as faults and diabase dikes, also influence the regional relief and, consequently, the landscape of the basin. Allied to these characteristics, different activities related to land use were observed in the Tatuí River Watershed, focusing on elements related to the urban area, the impact of soil sealing and surface runoff, which frequently result in flood events and mass movements.